Epinets : the Epistemic Structure and Dynamics of Social Networks. - Moldoveanu, Mihnea (Stanford University Press, 2014)
Epinets presents a new way to think about social networks, which focuses on the knowledge that underlies our social interactions. Guiding readers through the web of beliefs that networked individuals have about each other and probing into what others think, this book illuminates the deeper character and influence of relationships among social network participants. Drawing on artificial intelligence, the philosophy of language, and epistemic game theory, Moldoveanu and Baum formulate a lexicon and array of conceptual tools that enable readers to explain, predict, and shape the fabric and behavi.